2017
DOI: 10.1155/2017/1032846
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Survey, Characterization, and Expression Profile Analysis of the SBP Genes in Pineapple (Ananas comosus L.)

Abstract: Gene expression is regulated by transcription factors, which play many significant developmental processes. SQUAMOSA promoter-binding proteins (SBP) perform a variety of regulatory functions in leaf, flower, and fruit development, plant architecture, and sporogenesis. 16 SBP genes were identified in pineapple and were divided into four groups on basis of phylogenetic analysis. Five paralogs in pineapple for SBP genes were identified with Ka/Ks ratio varied from 0.20 for AcSBP14 and AcSBP15 to 0.36 for AcSBP6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Pineapple ( Ananas comosus L.) is the second most economically important fruit crop in the world after banana, and the improvement of its qualities are aimed at increasing yield, taste and resistance to environmental changes [ 1 ]. It is a monocotyledonous triploid fruit that belongs to the family Bromeliaceae [ 2 4 ]. Pineapple exhibits crassulacean acid metabolism (CAM) and has been used as a model to study the CAM pathway [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pineapple ( Ananas comosus L.) is the second most economically important fruit crop in the world after banana, and the improvement of its qualities are aimed at increasing yield, taste and resistance to environmental changes [ 1 ]. It is a monocotyledonous triploid fruit that belongs to the family Bromeliaceae [ 2 4 ]. Pineapple exhibits crassulacean acid metabolism (CAM) and has been used as a model to study the CAM pathway [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genome sequencing of pineapple was completed in 2015 [32], which laid the foundation of the functional study of genes and their relationships. The genome-wide association studies of some TF families have been conducted and reported in pineapple, such as SBP [33], WRKY [34], and DOF [35]. However, the bZIP gene family of pineapple has not yet been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Pineapple plants were MD2 propagated by tissue culture [30] and were supplied by Haixia institute of science and technology Centre for Genomics and Biotechnology, Fujian Agriculture and Forestry University, Fuzhou, China. Plastic pots containing soil mixture (peat moss: perlite = 2:1 ( v / v )) were used for pineapple plants and grown in a growth house at 30 °C temperature and 60–70 mMolL −1 photons m –2 s −1 with 70% humidity and 16/8 h light cycle [9,31,32]. All the Arabidopsis plants used in this research were in background Colombia.…”
Section: Methodsmentioning
confidence: 99%